SISTEM PAKAR MENDIAGNOSA PENYAKIT GIGI DAN MULUT SERTA KEBUTUHAN PERAWATNNYA - Kusnanto, Gery; Habib, Ahmad; Ardiyanti, Christin (Informatics, Universitas 17 Agustus 1945 Surabaya, 2015)
Dental disease is the most often disease which is complained by Indonesian people due to the passiveness of dental healthy. A person’s dental healthy obviously takes impact to others organs and up until now dental healthy not being the main concern yet. Therefore, it is required an application which could assist dentist and assistant’s work in diagnosing and providing beneficial information to the people about the important of dental healthy. That application is in the form of expert system by using forward chaining method. Expert system diagnoses dental disease and mouth including the treatment needed. Hopefully this application could assist people in diagnose dental disease and mouth, so that could resulting the precise way of healing along with giving dental health information about the way to treat dental properly.Keywords : Encyclopedia, Historic Buildings, Android.